Impact of Sevoflurane and Propofol on Pediatric Laryngeal Reflexes During Anesthesia Induction - Mohammed Ali Ibrahim Kareem Al-jibawi; Karrar Abed Almonem Hadi Maki Alkhafagy; Mahir Hussein Hasan AlSaadawi (Academia Open, 2023)
This study aimed to investigate the influence of sevoflurane and propofol anesthesia, administered at two distinct levels of hypnosis, on laryngeal reflexes in children aged 2 to 6 undergoing surgery. Seventy participants were randomly assigned to receive either sevoflurane or propofol anesthesia, and their responses to laryngeal irritation were evaluated. Results revealed that regardless of the level of hypnosis, sevoflurane anesthesia led to a higher incidence of laryngospasm apnea compared to propofol anesthesia, with some episodes lasting over five seconds. Conversely, children receiving propofol anesthesia exhibited more frequent exhalation and coughing responses. These findings highlight the importance of appropriate anesthetic dosages in pediatric cases, as the choice of anesthetic agent can significantly impact airway defense reflexes, with potential clinical implications for airway management during anesthesia induction in children. Highlights : Sevoflurane anesthesia in children aged 2 to 6 is associated with a higher incidence of laryngospasm apnea compared to propofol anesthesia, emphasizing the need for careful anesthetic selection in pediatric cases. Propofol anesthesia induces more frequent exhalation and coughing responses, suggesting potential advantages in airway management during anesthesia induction in children. This study underscores the critical role of appropriate anesthetic dosages in mitigating the risk of exaggerated airway defense reflexes and ensuring patient safety during pediatric surgery. Keywords : Pediatric anesthesia, Sevoflurane, Propofol, Laryngeal reflexes, Airway management